2013
DOI: 10.1186/1742-4755-10-36
|View full text |Cite
|
Sign up to set email alerts
|

The role of community-based health planning and services strategy in involving males in the provision of family planning services: a qualitative study in Southern Ghana

Abstract: BackgroundReproductive health and Family Planning (FP) services have been of global concern especially in developing countries where fertility rates are high. Traditionally FP services had always targeted females with little or no attention given to males. To ensure equitable distribution of health services, Ministry of Health (MOH), Ghana adopted the Community-Based Health Planning and Services (CHPS) as a nationwide health policy with the aim of reducing obstacles to physical and geographical access to healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 21 publications
6
90
0
1
Order By: Relevance
“…The Community-based Health Planning and Services (CHPS) may be one such contributing factor [6264]. This is a national health policy initiative adopted in 1999 that aims to reduce geographical barriers making access to health care difficult in Ghana by mainly focusing on deprived rural districts in remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…The Community-based Health Planning and Services (CHPS) may be one such contributing factor [6264]. This is a national health policy initiative adopted in 1999 that aims to reduce geographical barriers making access to health care difficult in Ghana by mainly focusing on deprived rural districts in remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…In effect, women who cannot overcome fear of spousal abandonment or neglect in case of method complications may likely opt not to use contraception until their spouse agrees to it. A recent study in southern Ghana revealed that spousal consent was still very relevant in contraceptive uptake among women (11). Programs should therefore be designed to target men to discredit these misconceptions.…”
Section: Discussionmentioning
confidence: 99%
“…However, records indicate that Ghana’s current contraceptive acceptance rate is 23%, five percentage points below the expected projection. Several factors may be responsible for Ghana’s inability to achieve this target, notably barriers in contraceptive use that have often been cited as one of the reasons impeding the achievement of fertility regulations (11). Understanding these barriers is important for providing programing guidance on the provision of family planning services.…”
Section: Introductionmentioning
confidence: 99%
“…This picture is similar to findings in Nigeria, Ghana, Democratic Republic of Congo (DRC) and Ethiopia. 3,4,20,21 Some modern female FP methods are expensive and therefore tend to dissuade men from being involved. Also, since some men are ignorant or do not have adequate information about FP, their involvement is affected to the same extent.…”
Section: Barriers To Male Involvement In Family Planningmentioning
confidence: 99%